صعوبات تدريس التعبير الشفوي في مرحلة التعليم الأساسي من وجهه نظر معلمي المادة - النجار، المهدي علي المهدي (جامعة مصراتة - كلية التربية, 2021)
هدفت الدراسة إلى التعرف على صعوبات تدريس التعبير الشفوي في مرحلة التعليم الأساسي من وجهه نظر معلمي المادة. ولتحقيق أهداف الدراسة أعد الباحث استبانة تألفت من مجموعة من الفقرات، وبعد التأكد من صدقها وثباتها وزعت على عينة الدراسة المكونة من مجموعة من معلمي المادة في مرحلة التعليم الأساسي والبالغ عددهم (35) معلما ومعلمة، موزعين على مختلف مدارس مدينة مصراته، حيث تم اختيارهم بطريقة عشوائية، وتم معالجة البيانات إحصائيا باستخدام البرنامج الإحصائي (SPSS). وقد أظهرت النتائج أن الرأي السائد بمجتمع الدراسة يكون إما أنها صعوبات بدرجة متوسطة أو كبيرة؛ مما يدل على وجود هذه الصعوبات، مع مراعاة ترتيبها؛ الأمر الذي يستدعي معالجتها، وأخذها بعين الاعتبار، خاصة تلك التي تكون بدرجة كبيرة. فجاءت أعلى الفقرات من حيث الوسط الحسابي، الفقرة التي تنص على أن الخوف والخجل اللذان يصيبان التلميذ عند مطالبته بالتعبير الشفوي، أما أقل الفقرات من حيث الوسط الحسابي فهي الفقرة التي تنص على قلة عدد الموضوعات التي تعطى للتلميذ خلال السنة الدراسية في المراحل الابتدائية. وقد أوصت الدراسة بجملة من التوصيات أبرزها ضرورة الاهتمام بتعليم مادة التعبير بنوعيه الشفوي والتحريري، خاصة في الصفوف الأولى من مرحلة التعليم الأساسي؛ كونها حجر الأساس في تعليم درس التعبير. The study aimed to identify the difficulties of teaching oral expression in basic education from the point of view of subject teachers. To achieve the objectives of the study, the researcher prepared a questionnaire consisting of a set of paragraphs, and after verifying its validity and reliability, it was distributed to the study sample, which consisted of a group of (35) teachers of the subject in the basic education stage, distributed among the various schools of the city of Misurata. Random and the data was statistically processed using the statistical program (SPSS). The results showed that the prevailing opinion in the study community is either that they are difficulties of a medium or great degree; Which indicates the existence of these difficulties, taking into account their arrangement; Which calls for addressing and taking them into consideration, especially those that are to a large extent The highest paragraphs came in terms of the arithmetic mean, the paragraph that states that fear and shyness affect the student when he asks for oral expression, while the lowest paragraphs in terms of the arithmetic mean are the paragraph that states the small number of topics given to the student during the school year in the primary stages. The study recommended a number of recommendations, most notably the need to pay attention to teaching oral and written expression, especially in the first grades of the basic education stage. Being the cornerstone in teaching the lesson of expression.
Keywords: الإدارة التعليمية -- اللغة العربية -- معلمو المدارس -- طرق التدريس